The Fruits of Labor: Home Food Procurement and Mental Health in the Time of COVID-19. Issue 3 (4th May 2023) - Wirkkala, Kristen Brassard; Niles, Meredith T.; Belarmino, Emily H.; Bertmann, Farryl
ABSTRACT: We examine the relationship of home food procurement (HFP) during COVID-19 to emotional eating and stress using a statewide representative survey (n = 600) in Vermont. Women and people with a job change since COVID-19 were more likely to experience higher stress and emotional eating. Engaging in HFP, especially gardening, is associated with less emotional eating. However, people who fished, hunted, or canned more since the pandemic began were more likely to eat for emotional reasons and experience higher stress. These results suggest that gardening, even during a pandemic, may contribute to stress reduction, more so than other nature-based food production activities.